Innovation and employment - Marco Vivarelli (IZA World of Labor, 2015)
Studies find that technological change has contributed to the decline in manufacturing and to persistent unemployment in many advanced economies. While process innovation can be job-destroying, product innovation can imply the emergence of new firms, new sectors, and thus new jobs. But even for process innovation, the final impact on labor demand is shaped by market mechanisms that can compensate for the direct job-destroying impact if market and institutional rigidities do not impede them. Policies should maximize the job-creation effect of product innovation and minimize the direct labor-saving impact of process innovation.
Keywords: O33; J21; 330; innovation; technological change; R&D; employment; technological unemployment